No cry at birth: global estimates of intrapartum stillbirths and intrapartum-related neonatal deaths - Joy Lawn; Kenji Shibuya; Claudia Stein (The World Health Organization, 2005)
OBJECTIVE: Fewer than 3% of 4 million annual neonatal deaths occur in countries with reliable vital registration (VR) data. Global estimates for asphyxia-related neonatal deaths vary from 0.7 to 1.2 million. Estimates for intrapartum stillbirths are not available. We aimed to estimate the numbers of intrapartum-related neonatal deaths and intrapartum stillbirths in the year 2000. METHODS: Sources of data on neonatal death included: vital registration (VR) data on neonatal death from countries with full (> 90%) VR coverage (48 countries, n = 97 297); studies identified through literature searches (> 4000 abstracts) and meeting inclusion criteria (46 populations, 30 countries, n = 12 355). A regression model was fitted to cause-specific proportionate mortality data from VR and the literature. Predicted cause-specific proportions were applied to the number of neonatal deaths by country, and summed to a global total. Intrapartum stillbirths were estimated using median cause-specific mortality rate by country (73 populations, 52 countries, n = 46 779) or the subregional median in the absence of country data. FINDINGS: Intrapartum-related neonatal deaths were estimated at 0.904 million (uncertainty 0.65-1.17), equivalent to 23% of the global total of 4 million neonatal deaths. Country-level model predictions compared well with population-based data sets not included in the input data. An estimated 1.02 million intrapartum stillbirths (0.66-1.48 million) occur annually, comprising 26% of global stillbirths. CONCLUSION: Intrapartum-related neonatal deaths account for almost 10% of deaths in children aged under 5 years. Intrapartum stillbirths are a huge and invisible problem, but are potentially preventable. Programmatic attention and improved information are required.